Feeding Difficulties among Preschool Children in Udupi: A Cross-Sectional Survey - Jevita Dsouza; Rupambika Sahoo; Sumita Rege (Indian Journal of Community Medicine)
Feeding is an important task for young children essential for fostering sensory, motor, and social skills for their overall well-being and functional independence. Globally, feeding problems in typically developing children are reported to range from 17.5% to 49.2%. The aim of this study was to determine the prevalence of feeding difficulties in preschool children in Udupi. Also, the strategies used for children with feeding difficulties were identified. A cross-sectional study design was implemented in preschools of Udupi. The Behavioural Paediatric Feeding Assessment Scale (BPFAS) was administered to caregivers of 217 pre-schoolers of Udupi town to identify the prevalence of feeding difficulties. An open ended question about the strategies employed for feeding their children was also included in the questionnaire. Descriptive statistics were employed to analyse the data. The results showed a high prevalence of feeding difficulties i.e. 47.5% and 55.76% according to the Total Feeding Scores (TFS) and Total Problem Scores (TPS) respectively, based on the BPFAS. Parents used various behavioural and other strategies to feed their children. The findings of the study highlight the high prevalence of feeding issues among pre-schoolers. Thus, it is important to create awareness among caregivers of typically developing children and provide interventions to both the child as well as the caregivers involved in feeding.